Freeze-drying: perceptions and challenges for drying foodstuffs and plant extracts - SALAMANCA, Constain; ROJAS, John (Vitae, 2015)
One of the most important features of foodstuffs and plant extract-based products is related to their fragile stability, especially when exposed to several ambient factors such as air, light radiation, heat and water vapour. The latter may contribute to the increase of free or bound water associated to the product. In this scenario, these variables may lead to different phenomena such as self-oxidation and hydrolysis of functional compounds and thus, a considerable inconsistency of products where these substances are part of occurs.